2021
DOI: 10.1186/s13287-021-02353-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-grade human dental pulp stem cells suppressed the activation of osteoarthritic macrophages and attenuated cartilaginous damage in a rabbit osteoarthritis model

Abstract: Background Although increasing evidence has demonstrated that human dental pulp stem cells (hDPSCs) are efficacious for the clinical treatment of skeletal disorders, the underlying mechanisms remain incompletely understood. Osteoarthritis (OA) is one of the most common degenerative disorders in joints and is characterized by gradual and irreversible cartilaginous tissue damage. Notably, immune factors were newly identified to be closely related to OA development. In this study, we explored the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…DPSCs have been applied in articular hyaline cartilage tissue regeneration and tissue engineering [ 189 ]. It was demonstrated that human DPSCs suppressed OA macrophage activation in a direct co-culture system in vitro and attenuated damage to the articular cartilage in a rabbit knee OA model in vivo [ 190 ]. Local injection of DPSCs in a model of rats with temporomandibular joint (TMJ) arthritis relieved hyperalgesia and synovial inflammation and attenuated cartilage matrix degradation, according to histologic staining and μCT scanning results [ 191 ].…”
Section: Dental Pulp Stem Cellsmentioning
confidence: 99%
“…DPSCs have been applied in articular hyaline cartilage tissue regeneration and tissue engineering [ 189 ]. It was demonstrated that human DPSCs suppressed OA macrophage activation in a direct co-culture system in vitro and attenuated damage to the articular cartilage in a rabbit knee OA model in vivo [ 190 ]. Local injection of DPSCs in a model of rats with temporomandibular joint (TMJ) arthritis relieved hyperalgesia and synovial inflammation and attenuated cartilage matrix degradation, according to histologic staining and μCT scanning results [ 191 ].…”
Section: Dental Pulp Stem Cellsmentioning
confidence: 99%
“…Among MSCs, DPSCs are also known to secrete powerful immunomodulatory and anti-inflammatory cytokines such as transforming growth factor-beta (TGF- β ), interleukin-8 (IL-8), interleukin-6 (IL-6), hepatocyte growth factor (HGF), and indoleamine 2,3-dioxygenase (IDO) [ 84 , 85 ]. In fact, DPSCs have been shown to significantly inhibit the activation of osteoarthritis macrophages in vitro and to reduce cell morphology, immune phenotype, and expression of inflammatory factors [ 86 ]. DPSC suppressed the activation of osteoarthritic macrophage in osteoarthritis [ 86 ].…”
Section: Neural Regeneration Of Dpscsmentioning
confidence: 99%
“…In fact, DPSCs have been shown to significantly inhibit the activation of osteoarthritis macrophages in vitro and to reduce cell morphology, immune phenotype, and expression of inflammatory factors [ 86 ]. DPSC suppressed the activation of osteoarthritic macrophage in osteoarthritis [ 86 ]. Also, the monocytic mobilizing protein-1 (MCP-1) and the secretory external domain of sialic acid-binding Ig-like lectin-9 (ED-Siglec-9) secreted from DPSCs promoted recovery after rat SCI [ 87 ].…”
Section: Neural Regeneration Of Dpscsmentioning
confidence: 99%
“…In this context, human dental pulp stem cells (hDPSCs) have been proven as an effective cell source in regenerative medicine due to their multipotential capabilities, donor accessibility, and low cost [10]. hDPSCs display the ability to differentiate into several lines and chondrocytes in particular [11].…”
Section: Introductionmentioning
confidence: 99%